2005
DOI: 10.1038/nsmb929
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of TEA blockade in a model potassium channel

Abstract: Potassium channels catalyze the selective transfer of potassium across the cell membrane and are essential for setting the resting potential in cells, controlling heart rate and modulating the firing pattern in neurons. Tetraethylammonium (TEA) blocks ion conduction through potassium channels in a voltage-dependent manner from both sides of the membrane. Here we show the structural basis of TEA blockade by cocrystallizing the prokaryotic potassium channel KcsA with two selective TEA analogs. TEA binding at bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
175
2
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(195 citation statements)
references
References 41 publications
16
175
2
2
Order By: Relevance
“…Potentiation of diltiazem binding by Ca 2ϩ (7) suggests that the ammonium group binds at the focus of P-helices in the presence of Ca 2ϩ . This model is consistent with the x-ray structures of KcsA-TBA co-crystals (42,48) and models of Na ϩ channels with local anesthetics (32,40).…”
Section: Channelsupporting
confidence: 86%
“…Potentiation of diltiazem binding by Ca 2ϩ (7) suggests that the ammonium group binds at the focus of P-helices in the presence of Ca 2ϩ . This model is consistent with the x-ray structures of KcsA-TBA co-crystals (42,48) and models of Na ϩ channels with local anesthetics (32,40).…”
Section: Channelsupporting
confidence: 86%
“…From mutagenesis studies, it has been shown that external TEA blockage is dependent upon the presence of amino acids with an aromatic side chain located near the extracellular entrance to the pore [23]. TEA ethyl groups interact simultaneously with the tyrosine side chains of the selectivity filter on all four subunits and make favorable electrostatic interactions and van der Waals contacts with the edge of the aromatic ring [24]. Similar to TEA, pore blocker toxins possess a 'functional dyad' composed of a lysine and tyrosine residue (6)(7) A distant to each other) that contributes to the blockage of the ion flux [25].…”
Section: Discussionmentioning
confidence: 99%
“…We used TEA ions to probe for any inner pore structural changes that might have been caused by these mutations. TEA acts as a classic pore blocker, interacting at the extracellular mouth of the selectivity filter in K ϩ channels to obstruct K ϩ flux (22)(23)(24)(25). TEA can therefore be used as a "molecular caliper" to probe the dimensions of the inner pore under different conditions.…”
Section: The His Residue In the Outer Pore Turret Also Contributed Tomentioning
confidence: 99%